[Complementary Strategy of RSVpreF Vaccination/Nirsevimab versus Nirsevimab Alone for the Prevention of RSV Infection in Infants in Italy: A Cost-Minimization Analysis] - Colombo, Giorgio Lorenzo; Novelli, Giuseppe (Farmeconomia. Health Economics and Therapeutic Pathways, 2025)
OBJECTIVE: To assess the economic impact of two preventive strategies against respiratory syncytial virus (RSV) infection in Italian newborns: universal administration of nirsevimab versus a complementary approach combining maternal RSVpreF vaccination and selective use of nirsevimab. METHODS: A cost-minimization analysis was conducted over a 3-year time horizon, based on the assumption of equal clinical efficacy between the two strategies, as supported by published evidence. The analysis compared: (1) the exclusive use of nirsevimab in all newborns, and (2) a complementary strategy with RSVpreF vaccination during pregnancy for infants born in the RSV season (October–March), combined with targeted use of nirsevimab for extremely and very preterm infants and for those born outside the protective window of maternal immunization. Only drug acquisition costs were included, assuming equivalent healthcare resource use in both scenarios. Epidemiological and cost data were derived from national birth statistics, literature, and public pricing sources. RESULTS: Assuming a birth cohort of 379,890 infants per year and 70% coverage, the annual cost of universal nirsevimab administration (Scenario 1) was €61,162,290, amounting to €183,486,870 over three years. In the complementary strategy (Scenario 2), annual costs were €55,062,016, totaling €165,186,049. This represents a saving of €6.1 million per year and €18.3 million over three years, equivalent to a 10% reduction in expenditure. CONCLUSIONS: In the Italian context, a complementary RSV prevention strategy combining maternal vaccination with targeted neonatal immunization may offer substantial cost savings for the national health system, without compromising clinical efficacy. These findings support the implementation of integrated and flexible immunization programs and highlight the potential role of maternal RSV vaccination in enhancing both sustainability and effectiveness of public health strategies.